Computational Studies on 5-(4-(4-(Diphenylamino)Phenylamino) phenyl)-2-Cyanopenta-2, 4-enoic Acid for dye Sensitized Solar cell Application. (2015) - Mohankumar, V.; Kotteswaran, S.; Pandian, M. Senthil; Ramasamy, P.
Abstract: Dye-sensitized solar cells have gained widespread interest for their potential as low-cost solar energy conversion devices. In this paper, we present a computational study of 5-(4-(4-(diphenylamino)phenylamino) phenyl)-2-cyanopenta-2, 4-enoic acid dye using density functional theory (DFT) and Time dependent density functional theory (TD-DFT) method with B3LYP/6-31G(d, p) level basis set. The structural geometry, orbitals energy, polarizability and hyperpolarizability of this dye were studied. The calculated HOMO and LUMO energy gap shows that the charge transfer occurs in the sensitizer. The calculated results of this dye demonstrate that this dye can be used as potential sensitizer with TiO2 and (I-/I3-) electrolyte for DSSC.